30 Crash risk associated with distracted driving. (9th June 2015) - Blanar, Laura; Kaufman, Robert; Qiu, Qian; Maeser, Jennifer; Freedheim, Amy; Kirk, Annie Phare; Ebel, Beth E.
Abstract : Introduction: Distracted driving is increasingly common and is associated with crash risk. Washington State has enacted laws to prohibit texting or talking on a handheld phone while driving. This study examined the association between distracted driving citations (inattention, texting, or talking on a handheld phone) and crash risk. Methods: We conducted a case control study of licensed drivers in six large Washington counties (two-thirds of the state population). Distracted driving citations were linked to statewide police crash records and Department of Licensing records for 2012. Study subjects were licensed drivers age 15 years and above. We examined the association between distraction-related citations and crash risk using Poisson regression. Results: Among the 3.5 million licensed drivers in 2012, 30 per thousand licensed drivers were involved in a crash. The annual rate of distracted driving citation was 10.7 per thousand. Among drivers cited for distraction, 16% crashed in the same year (10% cited at the time of crash, 6% crashed on another date). Adjusted for age, gender and county, elevated crash risks were associated with any distracted driving citation (RR 5.27, 95% CI 5.13, 5.41), a citation for inattention (RR 13.45 95% CI 13.01, 13.09), texting (RR 2.82, 95% CI 2.38, 3.34, ) and talking on a cell phone (RR 2.53, 95% CI 2.43, 2.64). The association between distraction citations and crash risk was higher for drivers under age 17 and highest for ages 18–25, compared to drivers age 26–44. In contrast to most driving risk factors, female drivers who received distracted driving citations were at greater risk of crash than male drivers. Conclusions: Drivers cited for texting, talking on a cell phone or inattentive driving were much more likely to be involved in a police-reported crash. Stronger enforcement of distracted driving laws holds promise for reducing crash risk.